The Declining Importance of Tradable Goods Manufacturing in Australia and New Zealand : How Much Can Growth Theory Explain? - Hunt, Benjamin (IMF Working Papers; Working Paper ;, 2009)
In this paper, the IMF's new Global Economy Model (GEM) is used to estimate the contribution of unbalanced growth to the decline in the share of goods production in Australia and New Zealand. The simulation results suggest that faster productivity growth in the tradable goods sector in Australia, New Zealand, and their major trading partners accounts for a significant portion of the relative decline in the importance of goods production. Over the 1995 to 2004 period, unbalanced growth explains more than 80 percent of the decline in goods production in both countries.